Styles of Thought on the Continental Drift Debate - Pellegrini, Pablo Ariel (2019)
The continental drift controversy has been deeply analysed in terms of rationalist notions, which seem to find there a unique topic to describe the weight of evidence for reaching consensus. In that sense, many authors suggest that Alfred Wegener’s theory of the original supercontinent Pangea and the subsequent continental displacements finally reached a consensus when irrefutable evidence became available. Therefore, rationalist approaches suggest that evidence can be enough by itself to close scientific controversies. In this article I analyse continental drift debates from a different perspective which is based on styles of thought. I’ll argue that continental drift debate took much longer than it was usually recognized with two styles of thought coexisting for hundreds of years. These were fixism and mobilism and they were always confronting their own evidence and interpretations and functioning as general frameworks for the acceptability of a specific theory. Therefore, this text aims to bring much broader sociological elements than usually involved in the analysis of the continental drift theory.